Synergistic metabolic benefits of an exenatide analogue and cholecystokinin in diet‐induced obese and leptin‐deficient rodents. Issue 1 (14th October 2014) - Trevaskis, J. L.; Sun, C.; Athanacio, J.; D'Souza, L.; Samant, M.; Tatarkiewicz, K.; Griffin, P. S.; Wittmer, C.; Wang, Y.; Teng, C.‐H.; Forood, B.; Parkes, D. G.; et al.
<x xml:space="preserve">Abstract</x> Aim To test the impact of cholecystokinin (CCK) plus either amylin or a glucagon‐like peptide‐1 receptor (GLP‐1R) agonist on metabolic variables in diet‐induced obese (DIO) rodents. Methods A stabilized acetylated version of CCK‐8 (Ac‐Y*‐CCK‐8), selective CCK1 receptor (CCK1R) or CCK2 receptor (CCK2R) agonists, amylin or the GLP‐1R agonist and exenatide analogue AC3174 were administered in select combinations via continuous subcutaneous infusion to DIO rats for 14 days, or Lepob/Lepob mice for 28 days, and metabolic variables were assessed. Results Combined administration of Ac‐Y*‐CCK‐8 with either amylin or AC3174 induced greater than additive weight loss in DIO rats, with the overall magnitude of effect being greater with AC3174 + Ac‐Y*‐CCK‐8 treatment. Co‐infusion of AC3174 with a specific CCK1R agonist, but not a CCK2R agonist, recapitulated the weight loss mediated by AC3174 + Ac‐Y*‐CCK‐8 in DIO rats, suggesting that synergy is mediated by CCK1R activation. In a 4 × 4 full‐factorial response surface methodology study in DIO rats, a synergistic interaction between AC3174 and the CCK1R‐selective agonist on body weight and food intake was noted. Co‐administration of AC3174 and the CCK1R‐selective agonist to obese diabetic Lepob/Lepob mice elicited a significantly greater reduction in percentage of glycated haemoglobin and food intake relative to the sum effects of monotherapy groups. Conclusions The anti‐obesity and antidiabetic potential of combined GLP‐1R and CCK1R agonism is an approach that warrants further investigation.